A Comparative Study of Auditory-Perceptual Speech Measures for the Early Detection of Mild Speech Impairments - Kuruvilla-Dugdale, Mili; Threlkeld, Katie; Salazar, Mary; Nolan, Gwen; Heidrick, Lindsey (Seminars in Speech and Language, 2019)
Background and Purpose The aim of the study was to compare transcription-based speech intelligibility and scaled speech severity for the detection of mild speech impairments, by studying these metrics across talkers with Parkinson's disease (PD), age- and sex-matched older adults, and younger adults. An additional aim was to determine the impact of listener experience on these clinical measures.Methods Fifteen speakers from each experimental group were asked to read aloud 11 randomly generated sentences from the Speech Intelligibility Test at their typical speaking rate and loudness. Two groups of four listeners each, stratified as experienced or inexperienced listeners based on their clinical experience, judged the sentence samples. To estimate intelligibility, both listener groups were asked to orthographically transcribe exactly what they heard for each sentence. For severity estimates, the listener groups were asked to rate the sentences for overall quality based on voice, resonance, articulation, and prosody, using a visual analog scale.Results Transcription-based intelligibility and scaled severity scores of the PD group differed significantly from those of the older and younger adults. Between-age group differences in intelligibility and scaled severity were not observed. Listener experience had an impact on scaled speech severity, but not speech intelligibility. Between-group differences in speech severity were driven by the inexperienced group and not the experienced listener group.Implications Both transcription-based intelligibility and scaled severity estimates appear to be sensitive to relatively mild speech impairments in PD. Obtaining scaled severity is less labor intensive than transcription; therefore, visual analog scaling may be the preferred paradigm for clinical use. However, listener experience and training are important considerations for scaling techniques to be implemented clinically.
Keywords: Parkinson's disease; dysarthria; speech intelligibility; speech severity; visual analog scale